Analisis Pengaruh Leverage,Profitabilitas dan Kebijakan Dividen Terhadap Keputusan Investasi Pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2020 - 2021 - Hadi Kurniawan; Citra Indah Merina (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
This research was conducted to prove whether leverage, profitability, and dividend policy affect investment decisions. With an investment decision, it means giving an answer on what line of business to enter, because there are many alternatives that can be implemented so that the owner's wealth is expected to increase. The population of this research is all mining companies listed on the IDX in 2020-2021. The sample selection used a purposive sampling technique and 28 samples were obtained. Data analysis used multiple linear regression analysis with IBM SPSS version 26. The results of this study proved that dividend policy has a positive effect on investment decisions, leverage and profitability variables have no effect on investment decisions.